Total Factor Productivity and Foreign Human Capital: Evidence from the Western Balkans (Journal of Economics, Law and Society, 2025)
The Western Balkan Six economies have advanced structural reforms to boost economic growth, create new jobs, and bring living standards closer to those in Europe. However, the Western Balkan residents continue to be encouraged to look for career and educational possibilities outside of the region due to the slow rate of convergence and the significant development gap with other European nations. Over the past ten years, the Western Balkan emigration rate has increased by 10%, and as a result, about one-fifth of the population now lives outside of the region. The high levels of emigration that continue can be extremely challenging for development. They may cause skill shortages and labor market distortions, which may discourage potential investors from making investments because they are unable to find the necessary skills. Gaining competitiveness, attracting investment, and navigating the area's ecological and digital transition all depend on human capital and a competent workforce that can meet the labor market's skill requirements and spur innovation. They are also important pillars of an economy's resilience and prosperity, which is important in light of the COVID-19 pandemic and the changing nature of the global environment.The goal of this paper is to examine how immigrants contribute to innovation in Western Balkans. Using Total Factor Productivity as a measure of innovation. The focus is on the Western Balkan countries (Albania, Bosnia and Herzegovina, Montenegro, North Macedonia and Serbia). The relationship between migration and innovation is examined not only at regional, but also at sectoral level. This makes it possible to quantify the direct impact of immigrants in the industry where they are really employed. To address the potential endogeneity of migration we adopt instrumental variable technique originally devised by Card (2001). Moreover, we carried out the analysis of human capital composition across sectors in Bosnia and Herzegovina. The offered recommendations can be used by policy makers when designing future policies.